Knowledge and Attitude of Travellers Regarding Yellow Fever Vaccination - Tiwari, Pramil; Ahlawat, Rajiv; Gupta, Gaurav (Indian Journal of Pharmacy Practice)
Background: A large number of Indians travel to yellow fever endemic countries for job opportunities. However, till date, little is known about their knowledge and attitude about yellow fever vaccine. This study was, therefore, carried out to determine the traveller’s knowledge and attitude regarding yellow fever vaccination. Method: A cross-sectional questionnaire-based study was carried out at an outpatient clinic for travellers. A total of 307 responses were collected from the travellers who visited the clinic for yellow fever vaccination, in a pre-designed standardized self-administered questionnaire. Result: The average age of travellers was 37.3±4.5 years. Most of the travellers (77%) were not aware of yellow fever before being advised for the vaccination. The most common reason for travelling abroad was a business trip (46%). Half of the travellers did not know about duration of protection from yellow fever vaccine. Approximately 90% of the travellers did not know about the etiology of yellow fever. Close to 40% of the travellers thought that yellow fever vaccine was effective in providing protection, while the rest didn’t possess adequate knowledge about its efficacy. Conclusion: Over three-fourths of the travellers were unaware of yellow fever infection and the vaccination. There is need of creating awareness regarding yellow fever among travellers.
Keywords: India; Travellers; Travel clinic; Yellow fever; Yellow fever vaccine